Evaluation of the Risks of Facial Nerve Damage in Orthognathic Surgery - Mohammad Khursheed Alam; Mohammad Younis Hajeer; Mohammed Ali Jawad Alghafli; Faisal Maqbul Salm Alazmi; Ali Mansour Ali Almansour; Nor Farid Bin Mohd Noor; Mahmood Sajedeen (Journal of Pharmacy and Bioallied Sciences, 2025)
Background: Orthognathic surgery is a corrective procedure to address skeletal and dental deformities. Despite its effectiveness, there is a risk of complications, including facial nerve injury. This study aims to evaluate the prevalence, risk factors, and outcomes associated with facial nerve injury in orthognathic surgery. Materials and Methods: A retrospective analysis was conducted on 120 patients who underwent orthognathic surgery between January 2019 and December 2023 at a tertiary care center. The study included bilateral sagittal split osteotomy (BSSO), Le Fort I osteotomy, and genioplasty procedures. Facial nerve function was assessed preoperatively and at intervals of 1 week, 1 month, and 6 months postoperatively using the House-Brackmann grading system. Risk factors such as operative duration, nerve handling, and surgeon experience were analyzed. Results: Of the 120 patients, 15 (12.5%) experienced transient facial nerve injury, while 2 (1.7%) had persistent deficits at 6 months. Patients undergoing BSSO had the highest incidence of nerve injury (15%), followed by Le Fort I osteotomy (8%) and genioplasty (5%). Extended operative time (>3 h) and inexperienced surgeons were significantly associated with increased risk (P < 0.05). Most injuries were classified as mild (Grade II) and resolved spontaneously within 3 months. Conclusion: Facial nerve injury is a rare but notable complication of orthognathic surgery, with most cases being transient and mild. Identifying and mitigating risk factors, such as minimizing operative time and ensuring surgeon expertise, can help reduce its occurrence. Further studies are warranted to explore long-term outcomes and preventive strategies.